GDP Performances, Sector’s Performances and Contribution to GDP of Northern Province during War and Post War Scenarios of Sri Lanka. (e-conference JUICE 2014) - Anojan, V. (International Conference JUICE 2014, University of Jaffna, 2014)
I am Vickneswaran Anojan, Final year graduating student, Department of Accounting, Faculty of Management Studies and Commerce, University of Jaffna. My fields of interest are taxation, accounting, liquidity & capital structure management, effective production, working capital management and comparing the financial performance If we take GDP performance and sector’s performance and contribution to GDP of Northern Province during war and post war scenarios of Sri Lanka. Every sector is much be needed to the county for the development. Here 2006, 2007, 2008 considers as during war period and 2010, 2011, 2012 as post war period. After the civil war of the country the number of development activities are taking by the respective authority to develop the country and Northern Province specially here we may consider the infrastructure such as road development, rail way road development, engineering faculty for Jaffna university, garments(MAS Holdings-Killinochchi, Omega Line-Vavuniya and etc…) new factory in the region, opening the number of banks, companies and financial institutions branches, development of the telecommunication sector, development of professional studies such as Chartered Accountancy, CIMA, CMA and AAT, reopening the factories, new building and other development to schools, micro finance to the business, residence to the displace people, resettlement to the war effected people and etc. Here the government of Sri Lanka and respective authority should know about the sector wise performance of the province to take the future successful development. The mainly the particular province needs employment opportunity through the business development. Accordingly to the my descriptive analysis confirmed that post war period has high mean value contribution to the GDP than during war period from the Northern Province and the sector wise the agriculture, industry and service have the high contribution to GDP in the period of post war. Here the service sector contributes highly than other two sectors in the both period as well as the industry achieved a rapid performance in the period of post war than during war period. From the findings it can be seen that post war contributions to GDP by the Northern Province is very good and high level. The Northern Province’s contributions to GDP continuously increasing than other province however Northern Province contributes at low level that mean least percentage contribution to GDP than other province which is not good remarks for the province due to that the government, NGOs, INGOs, respective authority, private sector and researchers should find the actual facts for low level contribution and the ways to increase the contribution from the sectors. The industry contributes a high level however the Northern Province has adequate, wealthy, and good resource for agriculture so the respective authority should try to take the necessary steps to develop and increase the agriculture production than other two sectors. Finally as a researcher it can be suggested that to the business people and investors to avoid to build the buildings as luxury which is not good investment if they invest in the agricultural related business specially agricultural farms, developing fishing activities and introduction of the new cultivation that will be the good investment. The government and financial assistance providers should try to give the low interest rate loan to small business, agricultural based business and diary business with minimum requirement, the government should try to give the more productivity seeds to the farmers from the foreign and the respective authority should try to give adequate training to the Northern Province business people specially about protection of post harvesting loss training should be needed to the farmers in the particular region. After the civil war the foreign tourist are much visiting to the Northern Province and also the province has much of tourist point so the business people also can give much consideration tourist business also like better transport, hotels and other related business. The Province has much resource and potential to increase their contribution to the GDP in the future.